Perencanaan Persediaan Menggunakan Metode Material Requirement Planning Dengan Bantuan Aplikasi Microsoft Excel: Studi Kasus Pada Toko Beras Putra Multazam - Kharomah, Astrid Dwi Niar; Burhany, Dian Imanina; Afriady, Arif (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Putra Multazam Rice Shop is a small medium enterprise that operates in the field rice trade. This rice shop sells various brands of rice. This shop has a problem with inventory planning because the shop often experiences problems with rice supplies, either excess or lack of inventory. The aim of this research is to help shop owners carry out inventory planning using the Material Requirement Planning method. The research method used is descriptive quantitative with a case study approach. The results of this research show that: (1) inventory calculations carried out by rice shops are currently less effective because they use simple and irregular calculations, (2) inventory planning using the Material Requirement Planning method produces sales forecasts for rice products in sacks in the month May-December 2024 which increases every month, namely for Kurmo rice in May it was 358, June 295, July 431, August 468, September 504, October 541, November 577, and December 614, for JM Super rice in May 217, June 220, July 222, August 225, September 227, October 230, November 233, and December 235; safety stock of 32 sacks of Kurmo rice and 27 sacks of JM Super; reordering is done after reaching safety stock, and (3) design of inventory planning input system using Material Requirement Planning method consisting of data input menu, safety stock and MRP report.